Cosmological constraints on interacting light particles. Issue 8 (17th August 2017) - Brust, Christopher; Cui, Yanou; Sigurdson, Kris
Abstract: Cosmological observations are becoming increasingly sensitive to the effects of light particles in the form of dark radiation (DR) at the time of recombination. The conventional observable of effective neutrino number, N_{\rm eff} N eff, is insufficient for probing generic, interacting models of DR. In this work, we perform likelihood analyses which allow both free-streaming effective neutrinos (parametrized byN_{\rm eff} N eff ) and interacting effective neutrinos (parametrized byN_{\rm fld} N fld ). We motivate an alternative parametrization of DR in terms ofN_{\rm tot} N tot (total effective number of neutrinos) andf_{\rm fs} f fs (the fraction of effective neutrinos which are free-streaming), which is less degenerate than usingN_{\rm eff} N eff andN_{\rm fld} N fld . Using the Planck 2015 likelihoods in conjunction with measurements of baryon acoustic oscillations (BAO), we find constraints on the total amount of beyond the Standard Model effective neutrinos (both free-streaming and interacting) ofΔ N_{\rm tot} < 0.39 Δ N tot < 0.39 at 2σ σ . In addition, we consider the possibility that this scenario alleviates the tensions between early-time and late-time cosmological observations, in particular the measurements ofσ_8 σ8 (the amplitude of matter power fluctuations at 8h^{-1} h −1 Mpc), finding a mild preference for interactions among light species. We further forecast the sensitivities of a variety of future experiments, including Advanced ACTPol (a representative CMB Stage-III experiment), CMB Stage-IV, and the Euclid satellite. This study is relevant for probing non-standard neutrino physics as well as a wide variety of new particle physics models beyond the Standard Model that involve dark radiation.